A $15 U.S. Minimum Wage: How the Fast-Food Industry Could Adjust Without Shedding Jobs. Issue 3 (2nd July 2016) - Pollin, Robert; Wicks-Lim, Jeannette
Abstract: We consider the extent to which U.S. fast-food businesses could adjust to an increase in the federal minimum wage from its current level of $7.25 an hour to $15 an hour without having to resort to reducing their workforce. We consider this issue through a set of simple illustrative exercises, whereby the US raises the federal minimum wage in two steps over four years, first to $10.50 within one year, then to $15 after three more years. We conclude that the fast-food industry could absorb the increase in its overall wage bill without resorting to cuts in their employment levels at any point over this four-year adjustment period. We find that the fast-food industry could fully absorb these wage bill increases through a combination of turnover reductions, trend increases in sales growth, and modest annual price increases over the four-year period. Working from the relevant existing literature, our results are based on a set of reasonable assumptions on fast-food turnover rates, the price elasticity of demand within the fast-food industry, and the industry's underlying trend for sales growth. We also show that fast-food firms would not need to lower their average profit rate during this adjustment period.